Hyperphosphorylated tau protein in the cerebrospinal fluid of patients with Alzheimer's disease and other dementias: preliminary findings - Hartmann,Ana Paula Barbosa Jeronimo (2004)
Alzheimer's disease (AD) is pathologically characterized by the accumulation of amyloid plaques and tau-associated neurofibrillary tangles in the cerebral tissue. The search for antemortem biomarkers is intense including analysis of cerebrospinal fluid (CSF) beta-amyloid and tau proteins concentrations seeking for an accurate and early diagnosis. Levels of hyperphosphorylated tau at threonine 181 were measured in the CSF of 34 patients with AD (19 with senile AD - SAD and eight with presenile AD - PSAD) and seven with other dementias (OD). The levels of CSF phosphotau were significantly higher in the AD patients compared to OD (AUC 0.812), with no association with severity of dementia, age of onset, duration of the disease or scores in the Mini-Mental State Examination. There were no differences of phosphotau levels between SAD and PSAD patients. These findings corroborate some previous studies and indicate that CSF phosphotau may help to differentiate AD from other dementias.